2018
DOI: 10.1007/s10068-018-0307-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chios mastic gum and exercise on physical characteristics, blood lipid markers, insulin resistance, and hepatic function in healthy Japanese men

Abstract: The effects of Chios mastic gum () and exercise on physical characteristics, blood lipid markers, insulin resistance, and hepatic function were investigated in healthy, non-smoking Japanese men aged ≥ 40 years. Participants were allocated to control (C, 5 g/day placebo powder, n = 7), mastic (M, 5 g/day mastic powder, n = 7), or mastic plus physical activity groups (M + PA, 5 g/day mastic powder and 30-min exercise three times/week, n = 7), and measurements were taken at baseline, 3 and 6 months. Serum triglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
0
12
0
4
Order By: Relevance
“…Overexpression of PEPCK gene or overactivation of the PEPCK enzyme can result in hyperglycemia and the development of diabetes [ 57 ]. Moreover, previous studies have also shown that healthy volunteers and diabetic mice receiving Chios Mastiha on a daily basis had lower blood glucose levels and reduced insulin resistance [ 41 , 44 , 58 ]. Our findings confirm the observations above regarding the anti-hyperglycemic and anti-diabetic actions of Chios Mastiha––contributing to the characterization of the biochemical mechanism that this action takes place, and uncovering novel mechanisms of interference of Mastiha with the glucocorticoid receptor signaling via triterpenoids-induced regulation of GR transcriptional activation, regulation of GR protein levels, and/or GCs synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of PEPCK gene or overactivation of the PEPCK enzyme can result in hyperglycemia and the development of diabetes [ 57 ]. Moreover, previous studies have also shown that healthy volunteers and diabetic mice receiving Chios Mastiha on a daily basis had lower blood glucose levels and reduced insulin resistance [ 41 , 44 , 58 ]. Our findings confirm the observations above regarding the anti-hyperglycemic and anti-diabetic actions of Chios Mastiha––contributing to the characterization of the biochemical mechanism that this action takes place, and uncovering novel mechanisms of interference of Mastiha with the glucocorticoid receptor signaling via triterpenoids-induced regulation of GR transcriptional activation, regulation of GR protein levels, and/or GCs synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies have confirmed its efficacy as a functional food for gastrointestinal disturbances or several modern lifestyle-related diseases of consumers who have been using mastic daily for many years in the form of chewing gum for oral health, or in powder or capsule [83][84][85].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of the candy group were in the middle of the control group and the gum-chewing group, and it seems that only the component of the gum can improve the physical performance and energy metabolism index. The candy and gum were mainly composed of xylitol, and a previous study showed that xylitol can retain moisture; hence, this might prevent oral dehydration [14]. Additionally, xylitol could benefit microorganisms such as health-promoting bacteria, glucose levels, and blood lipids [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…The candy and gum were mainly composed of xylitol, and a previous study showed that xylitol can retain moisture; hence, this might prevent oral dehydration [14]. Additionally, xylitol could benefit microorganisms such as health-promoting bacteria, glucose levels, and blood lipids [14][15][16]. Therefore, these benefits of xylitol may affect physical performance and the energy metabolism index.…”
Section: Discussionmentioning
confidence: 99%